Masculinity and femininity - Hristova, Gergana Nikolova (Проблеми на постмодерността, 2024)
The article examines the different interpretations of masculinity and femininity within the contexts of sociology, cultural studies, and psychology. In sociology, gender roles are considered to be socially constructed and variable, with feminist studies emphasizing the social construction of femininity in the context of gender inequality. In cultural studies, Hofstede views masculinity and femininity as cultural dimensions that influence societal attitudes and behavior. Overall, gender is interpreted as a complex of biological, social, and psychological aspects, which are expressed on a continuum and are often subject to social and cultural reconstruction. In psychology, these characteristics are associated with social and behavioral aspects, rather than with biological sex alone. Gender schema theory highlights that individuals can exhibit both masculine and feminine traits. Psychoanalysis introduces concepts of gender identity and the role of parents in the gender socialization of children.